Security Analysis Of AI-Based Mobile Application For Fraud - Valentino, Muhammad Ryan (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Fraud in digital transactions is increasing along with the development of technology. To address this issue, artificial intelligence (AI)-based mobile applications have been used in detecting and preventing fraudulent acts. This research aims to analyze the security of AI-based mobile applications in the context of fraud detection, as well as identify the weaknesses and challenges faced. The results of the analysis show that while AI-based applications have great potential in detecting fraud, there are several security risks that must be addressed, including data privacy issues and attacks on AI models. This study also provides recommendations to improve the security and effectiveness of applications in detecting fraud.